2019
DOI: 10.1051/e3sconf/20198701002
|View full text |Cite
|
Sign up to set email alerts
|

Speed Control of an Induction Motor Fed by an Inverter Using dSPACE Controller

Abstract: This paper presents the design and implementation of Inverter system for driving three phase Induction motor using DSPACE DS1104 controller with the controlling objective space vector pulse width modulation (SVPWM) technique. AC motor drives are commonly used over DC motor drives because of their more advantages. Induction motor is the most commonly used AC motor drive for various industrial and domestic applications. The project will be commenced by a basic understanding of SVPWM inverter, components used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…It was revealed that the linetoline voltage of the inverter was steady, and about 98% accuracy of the speed controller was obtained [11]. In addition, in [12] an open loop speed controller of 3ɸ IM was implemnetedusing a DSPACE DS1104 Controller. The motor was fed by an inverter, which was controlled by a SVPWM.Different ranges of speed were obtained by varying the duty cycles.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the linetoline voltage of the inverter was steady, and about 98% accuracy of the speed controller was obtained [11]. In addition, in [12] an open loop speed controller of 3ɸ IM was implemnetedusing a DSPACE DS1104 Controller. The motor was fed by an inverter, which was controlled by a SVPWM.Different ranges of speed were obtained by varying the duty cycles.…”
Section: Introductionmentioning
confidence: 99%
“…PWM inverter has its area of application in industrial motor drives and uninterrupted power supply (UPS) systems as it has excellent modes of speed control of the induction motor [11]. The high efficiency and superiority of induction motors over DC motors are factors responsible for the high rising of their usage in industries [12], [13]. With renewable energy on the increase in recent times, an inverter which serves as a link to the grid will continue to find application in this area as well [14].…”
Section: Introductionmentioning
confidence: 99%